Geoinformatics of Spring Water Quality in Small Village - Saraswati, Ratna; Taqyudin, Taqyudin; Pamungkas, Fajar Dwi; Wibowo, Adi (Faculty of Geography, Universitas Gadjah Mada, 2023)
Geoinformatics is spatial information based on characteristics and analysis regarding spatial data. Water is the main component of human life with clean water, especially drinking water found from various sources, including spring water. Water quality is a global standard as a chemical, physical, and biological parameter. The study aims to determine the potential spring water based on spatial analysis of water quality standards for potential use. The method used to determine the potential utilization of springs using geographic information system analysis. Data is based on the difference in height, slope, and distance from springs to settlements and discharge. Water quality samples are analyzed using mobile and laboratory tests. The result found that physical parameters from five locations, Sirah Citanggulun, Cikerebek, Cijati, Cijati 2, and Galumpit, have good quality to meet the utilization requirements, especially for water designation class. Chemically parameters, water quality, is relatively good based on several parameters such as pH, Nitrite, dissolved iron, and zinc, which do not exceed the required quality standard threshold. The biological parameters, five samples are contaminated by bacteria Escherichia coli and total coliform. Regarding the literature review, this research found that biological contaminants are unsuitable for drinking water, but it is still good to become another used. The research concluded that the spring water in a small village could become potential uses for drinking water based on the parameter of water quality for daily use, especially for drinking water, regarding biological parameters that spring water must be boiled to drink.